2018
DOI: 10.1016/j.ejpb.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of gellan-cholesterol nanohydrogels embedding baicalin and evaluation of their wound healing activity

Abstract: In the present work, the preparation, characterization and therapeutic potential of baicalin-loaded nanohydrogels are reported. The nanohydrogels were prepared by sonicating (S nanohydrogel) or autoclaving (A nanohydrogel) a dispersion of cholesterol-derivatized gellan in phosphate buffer. The nanohydrogel obtained by autoclave treatment showed the most promising results: smaller particles (∼362 nm vs. ∼530 nm), higher homogeneity (polydispersity index = ∼0.24 vs. ∼0.47), and lower viscosity than those obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…Full thickness skin grafts are commonly used to cover the fingertip soft tissue defects and in some case the use of autologous growth factor blood derivatives is mandatory . However, new compounds from natural source as well as synthetic polymeric approaches based on hyaluronic acid, named nanohydrogel, represent an intense and promising field of research . Previously, we documented the beneficial effects of flavonoids, in the treatment of chronic venous ulcerations and recently, it has been reported that, among the plethora of flavonoids, quercetin (Que) is able to promote wound healing process .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full thickness skin grafts are commonly used to cover the fingertip soft tissue defects and in some case the use of autologous growth factor blood derivatives is mandatory . However, new compounds from natural source as well as synthetic polymeric approaches based on hyaluronic acid, named nanohydrogel, represent an intense and promising field of research . Previously, we documented the beneficial effects of flavonoids, in the treatment of chronic venous ulcerations and recently, it has been reported that, among the plethora of flavonoids, quercetin (Que) is able to promote wound healing process .…”
Section: Introductionmentioning
confidence: 99%
“…1 However, new compounds from natural source as well as synthetic polymeric approaches based on hyaluronic acid, named nanohydrogel, represent an intense and promising field of research. 10,11 Previously, we documented the beneficial effects of flavonoids, in the treatment of chronic venous ulcerations 4 and recently, it has been reported that, among the plethora of flavonoids, quercetin (Que) is able to promote wound healing process. [12][13][14] On the other hand, oleic acid (OA), locally applied or took orally, is able to both modulate immune response and restore inflammatory acute phase in wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, proper formulation allowing for vehiculation through the skin and a controlled release would greatly add to the beneficial effects prolonging the action and taking the bioavailable concentrations relatively low.In recent years, several natural compounds have been tested for the topical treatment of skin disorders by use of a variety of transcutaneous delivery systems including lipophilic nanoparticles like liposomes [12], solid lipid nanoparticles [13,14], nanostructured lipid carriers, monoolein aqueous dispersions [15,16], ethosomes [17,18], and lecithin organogels [19,20]. Speed up of wound healing process by a nanohydrogel embedding an antioxidant compound like baicalin has been described that exhibited optimal performance for a complete skin restoration and inhibition of specific inflammatory markers [21].A variety of hydrophilic delivery systems have also been explored such as gelatin, the product of collagen hydrolysis, as it offers several advantages including the historical safe use in a wide range of medical applications, low costs, inherent electrostatic binding properties, and proteolytic degradability. In addition, gelatin versatility allows the design of different carrier systems, spanning from micro or nanoparticles, to fibers and hydrogels.…”
mentioning
confidence: 99%
“…In recent years, several natural compounds have been tested for the topical treatment of skin disorders by use of a variety of transcutaneous delivery systems including lipophilic nanoparticles like liposomes [12], solid lipid nanoparticles [13,14], nanostructured lipid carriers, monoolein aqueous dispersions [15,16], ethosomes [17,18], and lecithin organogels [19,20]. Speed up of wound healing process by a nanohydrogel embedding an antioxidant compound like baicalin has been described that exhibited optimal performance for a complete skin restoration and inhibition of specific inflammatory markers [21].…”
mentioning
confidence: 99%
“…Treatment of 3T3 cells with hydrogen peroxide and baicalin showed that baicalin counteracted the oxidative effect of hydrogen peroxide with a 95% cell viability, irrespective of the dosage administered (20, 10, 1 and 0.1 µg/mL). These results showed the excellent antioxidant capacity of baicalin [ 111 ].…”
Section: Cholesterol-based Compounds In Transdermal Drug Deliverymentioning
confidence: 98%